Understanding feminist anticipation through 'back-talk': 3 narratives of willful, deviant, and care-full co-design practices. (February 2022) - Korsmeyer, Hannah; Light, Ann; Grocott, Lisa
Highlights: Processes of anticipating futures are contained within present-day conditions of structural inequity and various forms of entrenched oppression. A feminist approach to anticipation engages with plurality and the background conditions and dominant norms that shape our practices. The development of co-design materials and relational considerations of design-led projects point to how feminisms become enacted through practice. Material 'back-talk' can assist anticipation by surfacing implicit assumptions held by stakeholders, participants, and designers/facilitators. Feminist anticipation is not just what we anticipate, but how we practice anticipation, to better enable collective deviation from the status quo. Abstract: This article explores how co-design workshops might engage with the conditions that constrain our anticipation of more just futures. We discuss how practitioner commitments to feminisms might contribute to more critical exploration. Rather than exploring what practitioners should be doing in feminist futures-focused co-design, we seek a better understanding of how this practice unfolds and evolves. Therefore, the article discusses feminist anticipation from the perspective of three, first-person narratives. These accounts explore how practitioner 'feminist tendencies' become manifested in co-design materials. We also explore how the multi-directional 'back-talk' of workshop materials mediates how stakeholders, participants and the designers themselves co-anticipate contested, deviant, and plural futures. Borrowing the words from feminist scholar Sara Ahmed, these stories from practice seek to both answer and provoke the question: how are we unmaking how hard it is to deviate from what is expected?